2015
DOI: 10.1037/a0037779
|View full text |Cite
|
Sign up to set email alerts
|

Distraction control processes in free recall: Benefits and costs to performance.

Abstract: How is semantic memory influenced by individual differences under conditions of distraction? This question was addressed by observing how participants recalled visual target words—drawn from a single category—while ignoring spoken distractor words that were members of either the same or a different (single) category. Working memory capacity (WMC) was related to disruption only with synchronous, not asynchronous, presentation, and distraction was greater when the words were presented synchronously. Subsequent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 96 publications
(213 reference statements)
4
56
2
Order By: Relevance
“…The role of the latter manifests in those with low attentional control due to their stage of cognitive development in the context of any sort of sound but, as shown in other recent studies, those with relatively good attentional control (adults) are more likely to only exhibit such diversion in the presence of unexpected deviants (Hughes et al, 2013), particularly salient stimuli (Röer et al, 2013), or when there is semantic overlap between irrelevant and relevant events (e.g., Beaman, 2004;Marsh, Sörqvist, Hodgetts, & Beaman, 2015). While serial rehearsal per se plays a role in both children and adults' disruptibility when a task involves serial rehearsal (cf.…”
Section: Discussionmentioning
confidence: 79%
“…The role of the latter manifests in those with low attentional control due to their stage of cognitive development in the context of any sort of sound but, as shown in other recent studies, those with relatively good attentional control (adults) are more likely to only exhibit such diversion in the presence of unexpected deviants (Hughes et al, 2013), particularly salient stimuli (Röer et al, 2013), or when there is semantic overlap between irrelevant and relevant events (e.g., Beaman, 2004;Marsh, Sörqvist, Hodgetts, & Beaman, 2015). While serial rehearsal per se plays a role in both children and adults' disruptibility when a task involves serial rehearsal (cf.…”
Section: Discussionmentioning
confidence: 79%
“…These two tasks additionally differ in terms of their emphasis on the serial order in which memoranda are maintained and reported; Immediate Serial Recall requires ordered recollection, while Item Recognition does not. To retain the requirement for item recall (as in Immediate Serial Recall), but without the emphasis on serial order of presentation, some researchers have instead used a Free Recall paradigm (Beaman & Jones, 1998; Marsh, Sorqvist, Hodgetts, Beaman, & Jones, 2015; Neely & LeCompte, 1999; Unsworth, Spillers, & Brewer, 2010) in which participants are allowed to remember and report items in whatever order they desire. Another factor differentiating WM paradigms regards the duration of the retention interval, with some tasks involving the assessment of memory (essentially) immediately after presentation (as in Immediate Serial Recall), and others imposing a longer, though still “short-term”, delay interval between initial presentation and retrieval (as in Delayed Serial Recall (e.g., Chein & Fiez, 2001; Farrell, 2006).…”
Section: Wm Tasks and Their Propertiesmentioning
confidence: 99%
“…The relevant explanation put forth to account for impaired memory performance in free recall paradigms is that of a source-monitoring error (Fernandes et al, 2007;Marsh et al, 2008;and Marsh et al, 2015 who also incorporate a working memory capacity account). Specifically, Marsh et al (2008) suggest that an internal-external source-monitoring error occurs when semantically related items are internally generated and then believed to have come from an external source.…”
Section: Discussionmentioning
confidence: 99%
“…Marsh et al (2008Marsh et al ( , 2009 assessed the effect of auditory distraction on free recall of visually presented semantically categorised lists of words. They showed that unattended distractors that were semantically related compared to unrelated to the to-be-remembered words increased intrusions on an immediate free recall test and, as others have also shown, reduced veridical recall of target items (Marsh, Beaman, Hughes, & Jones, 2012;Marsh, Sörqvist, Hodgetts, Beaman, & Jones, 2015). Specifically, meaningful irrelevant speech disrupted free recall more than non-meaningful speech, and this effect was amplified when the irrelevant speech was semantically related to the to-be-remembered information (Marsh, Hughes, & Jones, 2009).…”
mentioning
confidence: 86%